POTENTIAL OF SAMBAS SIAM ORANGE (Citrus nobilis var. microcarpa) LEAVES ETANOL EXTRACT AGAINST Escherichia coli - Irvandy, Muhammad Syifa; Zakiah, Mistika; Asseggaf, Syarifah Nurul Yanti Rizki Syahab; Mahyarudin, Mahyarudin; Mardhia, Mardhia (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Escherichia coli has virulence factors and is able to avoid host defenses, and is resistant to antibiotics. Increasing resistance requires alternative therapies, including natural ingredients. The potential that comes from West Kalimantan is the Siamese orange (Citrus nobilis var. microcarpa). All parts of this plant contain secondary metabolites that can be utilized, for example the leaves. The compounds contained in secondary metabolites have antibacterial properties. This study was to determine the antibacterial potential of the ethanol extract of Siamese orange leaves on the growth of Escherichia coli bacteria. Method The orange leaves were extracted using 70% ethanol then continued with phytochemical analysis and antibacterial activity testing using the disc diffusion method. The results of the phytochemical analysis showed that the ethanol extract of Siamese orange leaves contained phenolics, alkaloids, saponins, flavonoids, and steroids. Antibacterial activity testing at all concentrations showed no inhibition zone. Conclusion The ethanol extract of Siamese orange leaves did not have antibacterial activity on the growth of Escherichia coli bacteria.